Atenuação natural monitorada em latossolo contaminado por misturas de diesel e biodiesel - Colombo, Rafael (2010)
The using of biodiesel as fuel alternative source is showing promising potential all over the world due to quantitative and qualitative reduction of the levels of envinromental polution, and how strategy source of renovating energy in substitution towards Diesel. Besides biodiesel is a biodegradable fuel, its behavior related to biodegradation is still unknown in many kinds of soils. This study intended to know if differents concentrations of biodiesel added in Diesel fuel can change the degradation velocity by local microorganisms. The objective of this study was make use of natural attenuation to determine the percentual of biodegradability of differents percentage of biodiesel added in Diesel fuel on Passo Fundo soil. They were utilized seven differents percentagem: B0, B2, B5, B20, B50 , B75 and B100, and the soil from horizon B contaminated with these percentuals was molded in 21 bioreators, been 3 bioreators to each percentual. Bi-monthly collects were realized and analysed by Soxhlet Method and Cromatography Gas (GC). The results showed that there were degradation in contaminant residual purport by Soxhlet Method and total carbon in GC. Humidity is one of the factors that influenced on the biodegradation of the contaminant, and that the higher the saturation of soil with water or high humidity, the slower will be the action of soil microorganisms to biodegrade the contaminant. The results also show that temperature exerts a high influence on the biodegradation of the contaminant, getting become more evident when over 21°C. It was expected that the contaminant that contained highest percentage of biodiesel produced higher degradation when compared to the contaminant that contained minor percentage of Diesel, but the results of this study didn t confirm this hypothesis. To finish, the different percentage of biodiesel added to Diesel presented similar behavior in relation to its degradation